The Effect of Working Capital and Accounts Receivable Turnover on the Profitability of Retail MSMEs - Della Aria Ningsih; Laynita Sari (Research in Accounting Journal (RAJ), 2026)
This study aims to analyze the impact of working capital and accounts receivable turnover on the profitability of retail Micro, Small, and Medium Enterprises (MSMEs) in the North Padang District. This research was conducted because the management of working capital and accounts receivable constitutes a crucial factor influencing the financial performance and business sustainability of MSMEs. The study population consisted of all 1,369 retail MSME units in the North Padang District; a sample of 94 respondents was selected using the Yamane formula and convenience sampling. Primary data obtained directly from respondents were used for the analysis. Data analysis involved validity and reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination test, the F-test, and the t-test. The results indicate that working capital has a positive and significant partial effect on MSME profitability. Similarly, accounts receivable turnover has a positive and significant effect on MSME profitability. These findings suggest that more efficient working capital management and faster accounts receivable turnover enhance the ability of MSMEs to generate profit. The study's findings are expected to serve as a reference for MSME owners in improving the effectiveness of financial management to support sustainable business performance.